Use of polymyxin B with different administration methods in the critically ill patients with ventilation associated pneumonia: a single-center experience - Shi, Rupeng; Fu, Yuanyuan; Gan, Yujing; Wu, Danying; Zhou, Suming; Huang, Min (Frontiers in Pharmacology, 2023)
Background: Whether nebulized polymyxin B should be used as an adjunctive therapy or substitution strategy to intravenous polymyxin B for the treatment of ventilator-associated pneumonia (VAP) remains controversial. This study's aim is to evaluate the efficacy and safety of different administration ways of polymyxin B in the treatment of VAP caused by extensively drug-resistant gram-negative bacteria(XDR-GNB). Methods: This retrospective cohort study enrolled VAP patients caused by XDR-GNB treated with polymyxin B in the intensive care unit. Patients were categorized by the administration methods as intravenous (IV) group, inhaled (IH) group, and the intravenous combined with inhaled (IV + IH) group. Microbiological outcome and clinical outcome were compared in each group. The side effects were also explored.Results: A total of 111 patients were enrolled and there was no difference in demographic and clinical characteristics among the three groups. In terms of efficacy, clinical cure or improvement was achieved in 21 patients ( 55.3%) in the IV group,19 patients ( 50%) in the IH group, and 20 patients ( 57.1%) in IV+IH group (P = 0.815).All three groups showed high success rates in microbiological eradication, as 29 patients with negative cultures after medication in IH group. Among all the patients who had negative bacterial cultures after polymyxin B, the IH group had significantly shorter clearance time than the IV group (P=0.002), but with no significant difference in 28-day mortality. Compared with IV group, a trend towards a lower risk of acute kidney injury was observed in IH group (P=0.025).From the perspective of minimal systemic renal toxicity , nebulized polymyxin B as a substitution strategy to intravenous polymyxin B for the treatment of VAP caused by XDR-GNB is feasible.versus intravenous polymyxin B for the treatment of extensive drug-resistant Gram-negative ventilator-associated pneumonia in the critical illnesses: a multi-center matched case-control study.